Revisiting Tourism Through Virality: A Systematic Review of Key Psychological Drivers - Dina Mustaqin; Yunia Wardi (Penerbit Jurnal Indonesia, 2025)
In the evolving landscape of digital tourism, viral marketing has become a powerful strategy for influencing traveler behavior. However, its specific impact on revisit intention remains underexplored, especially through the psychological lenses of destination image and consumer satisfaction. This study conducts a Systematic Literature Review (SLR) of 42 peer-reviewed empirical studies published between 2015 and 2025 to examine how viral marketing indirectly affects tourists’ intention to revisit a destination.Findings indicate that viral marketing rarely influences revisit intention directly. Instead, it operates through mediating variables—primarily destination image and consumer satisfaction—either individually or in combination. The most consistent pattern observed is a sequential pathway: viral marketing shapes a positive destination image, which enhances consumer satisfaction, ultimately leading to increased revisit intention.These results underscore the importance for tourism marketers to design viral content that not only captures attention but also aligns with traveler expectations and fosters a favorable perception of the destination. Understanding this indirect influence provides valuable insights for building long-term destination loyalty through strategic digital engagement.